2021
DOI: 10.1136/thoraxjnl-2021-216949
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes and outcomes of SARS-CoV-2, influenza, RSV and seven other respiratory viruses: a retrospective study using complete hospital data

Abstract: BackgroundAn understanding of differences in clinical phenotypes and outcomes COVID-19 compared with other respiratory viral infections is important to optimise the management of patients and plan healthcare. Herein we sought to investigate such differences in patients positive for SARS-CoV-2 compared with influenza, respiratory syncytial virus (RSV) and other respiratory viruses.MethodsWe performed a retrospective cohort study of hospitalised adults and children (≤15 years) who tested positive for SARS-CoV-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
6
34
1
Order By: Relevance
“…Our results add to the growing literature base comparing similarities and differences in clinical disease progression of patients hospitalized with influenza and SARS-CoV-2 [42][43][44],…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Our results add to the growing literature base comparing similarities and differences in clinical disease progression of patients hospitalized with influenza and SARS-CoV-2 [42][43][44],…”
Section: Discussionsupporting
confidence: 58%
“…Our results add to the growing literature base comparing similarities and differences in clinical disease progression of patients hospitalized with influenza and SARS-CoV-2 [4244], and have three important implications for clinical care and health systems. First, shared predictors of mortality could be used to identify, target, and prioritize hospitalized patients who are at greatest risk of death for prevention (e.g.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…COVID-19 has similar symptoms resembling influenza, including fever, headache, muscle ache and symptoms in the upper respiratory system such as coughing. Studies have shown that mortality rates in case of COVID-19 infection with the wild type SARS-CoV-2 may be even higher than infection with winter respiratory viruses ( WHO, 2021 ; Hedberg et al, 2022 ). Overall, respiratory infection caused by either influenza, other respiratory viruses or COVID-19 can lead to serious complications such as cardiovascular events and bacterial co-infections that may be lethal ( Piroth et al, 2021 ; Hedberg et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%